Separation and Preconcentration of Copper Ion by Micelle-Mediated Extraction in Aqueous Samples - F. Ahmadi; A. Khanmohammadi; Z. Tavakoli (E-Journal of Chemistry)
Cloud point extraction (CPE) has been used for preconcentration of copper after the formation of a complex with 5, 5-diphenylimidazolidine-2-thione-,4-one (thiophenytoin) (DFID) and later analysis by flame atomic absorption spectrometry (FAAS) using octylphenoxypolyethoxyethanol (Triton X-114) as surfactant. The chemical variables affecting the separation phase and the viscosity affecting the detection process were optimized. At pH 5.7±0.3, preconcentration of only 15 mL of sample in the presence of 0.06% (w/v)Triton X-114 and 1.5 mM DFID permitted the detection limits of 1.5 ng mL−1 for copper. The enrichment factor was 39 for copper. The proposed method has been applied to the determination of copper in various samples and a standard reference material.